2009
DOI: 10.1021/tx800447b
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Cholesterol Carboxyaldehyde by the Reaction of Singlet Molecular Oxygen [O2 (1Δg)] as Well as Ozone with Cholesterol

Abstract: A few years ago, it was reported that ozone is produced in human atherosclerotic arteries, on the basis of the identification of 3beta-hydroxy-5-oxo-5,6-secocholestan-6-al and 3beta-hydroxy-5beta-hydroxy-B-norcholestane-6beta-carboxaldehyde (ChAld) as their 2,4-dinitrophenylhydrazones. The formation of endogenous ozone was attributed to water oxidation catalyzed by antibodies, with the formation of dihydrogen trioxide as a key intermediate. We now report that ChAld is also generated by the reaction of choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 78 publications
4
90
0
1
Order By: Relevance
“…Figure 5b shows cholesterol in pure CH 3 OH at a concentration of 725 μM. The peak at m/z 401 has been reported in previous literature as protonated 5-cholesten-3β-ol-7-one ( Figure 5a, structure of neutral in Scheme 1f), a well known COP [11,30]. This suggests that the peak at m/z 401 in the MALDI mass spectra represents a solution-based oxidation product.…”
Section: Solution Based Oxidationsupporting
confidence: 54%
See 2 more Smart Citations
“…Figure 5b shows cholesterol in pure CH 3 OH at a concentration of 725 μM. The peak at m/z 401 has been reported in previous literature as protonated 5-cholesten-3β-ol-7-one ( Figure 5a, structure of neutral in Scheme 1f), a well known COP [11,30]. This suggests that the peak at m/z 401 in the MALDI mass spectra represents a solution-based oxidation product.…”
Section: Solution Based Oxidationsupporting
confidence: 54%
“…Employing an internal calibration using known DHB and cholesterol fragmentation peaks, the accurate masses of the radical cation peaks were determined. [12] and Uemi et al [11] led to the deduction that solution oxidation products contain hydroperoxide structures (Scheme 1c and d). However, there is no source of molecular oxygen or peroxide in either the matrix or analyte when under the vacuum conditions of the mass spectrometer.…”
Section: Identification and Origin Of Oxidation Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…This secosterol-A concentration was further increased upon activation with PMA, suggesting that human leukocytes within atherosclerotic tissues are activated to produce an ozone-like oxidant ( 10 ). However, it has been recently reported that secosterol-A and -B were generated in an ozone-independent mann er via the Hock-cleavage of 5 ␣ -hydroperoxy cholesterol, which can arise from the singlet oxygen ene reaction with cholesterol ( 13,14 ). Secosterol-B is formed easily under acidic conditions in organic solvents ( 13,14 ), whereas secosterol-A is either not formed at all or is a minor component in the aqueous buffer ( 9 ).…”
Section: Formation Of Secosterols By Hl-60 Cellsmentioning
confidence: 99%
“…Although the mechanisms of formation of secosterol-A and -B and their oxidized derivatives in vivo are not completely understood, secosterol-A and -B have been also reported to be formed in an ozone-independent manner in organic solvents via Hock-cleavage of 5-hydroperoxy cholesterol, which can arise from the singlet oxygen ene reaction with cholesterol. 5,6) We also found that secosterol-B rather than secosterol-A was preferentially formed in an in vitro reaction of cholesterol and singlet oxygen. 7) On the other hand, Wentworth et al reported recently that only ozone can react with cholesterol to form secosterol-A in aqueous solution, and that other oxidants, such as singlet oxygen, form secosterol-B as a major product, but not -A.…”
mentioning
confidence: 59%